Chasing Amy [videorecording (Blu-Ray)] - Affleck, Ben, 1972-; Adams, Joey Lauren; Lee, Jason, 1970-; Ewell, Dwight (Miramax Acquisition, 2021)
Cult comic book artist Holden falls in love with fellow artist Alyssa, only to be thwarted by her sexuality, the disdain of his best friend Banky and his own Misgivings about himself. Offers a thoughtful, funny look at how perceptions alter lives and how obsession and self-doubt skew reality.